Medeltidens genus: Kvinnors och mäns roller inom kultur, rätt och samhälle. Norden och Europa ca 300-1500. (Kriterium, 2016)
"In discussions relating to their role during the Middle Ages, women are typically assumed to only have been "pawns in a political game dominated by men", or to have primarily acted as intermediaries of power. In this book, however, the varying expressions of power are studied by changing the focus from a political and economic exercise of power controlled by men, to an approach based on interaction and communication between the sexes. In this volume, gender is instead interpreted as a total social phenomenon comprising all spheres of medieval society. This approach provides new opportunities to investigate how power operated on different levels within a societal structure. Thus, power is neither seen as emanating from a centre nor as dominated by only one sex. Instead, it is regarded as an all-embracing societal web, woven through threads of mutual dependence between men and women. In this book, scholars belonging to various disciplines, such as history, history of arts and literary history, discuss how cooperation between the sexes found expression in culture, judicial spheres and social organisation. The contributions do not only consider the Nordic countries, but also how gender constructions were affected by, and transformed through, the influence of contemporary cultural, juridical and ideological currents in Europe.